2019
DOI: 10.1084/jem.20181621
|View full text |Cite
|
Sign up to set email alerts
|

Severe influenza pneumonitis in children with inherited TLR3 deficiency

Abstract: Autosomal recessive IRF7 and IRF9 deficiencies impair type I and III IFN immunity and underlie severe influenza pneumonitis. We report three unrelated children with influenza A virus (IAV) infection manifesting as acute respiratory distress syndrome (IAV-ARDS), heterozygous for rare TLR3 variants (P554S in two patients and P680L in the third) causing autosomal dominant (AD) TLR3 deficiency. AD TLR3 deficiency can underlie herpes simplex virus-1 (HSV-1) encephalitis (HSE) by impairing cortical neuron-intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
143
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 108 publications
9
143
0
7
Order By: Relevance
“…Four IEIs-GATA2 (Bigley et al 2011;Pasquet et al 2013;Sologuren et al 2018), IRF7 (Ciancanelli et al 2015), IRF9 (Hernandez et al 2018), and TLR3 (Lim et al 2019) deficiencies-have been shown to cause life-threatening influenza pneumonitis (Table 1). Autosomal dominant (AD) GATA2 deficiency is the only one of these IEIs leading to a pleiotropic syndromic disorder that manifests as a lack of multilymphoid and granulocyte-macrophage progenitors in the bone marrow, smaller numbers of dendritic cells (DCs), monocytes, T, B and NK lymphocytes in peripheral blood, and higher susceptibility to viral, mycobacterial, and fungal infections.…”
Section: Inherited Gata2 Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Four IEIs-GATA2 (Bigley et al 2011;Pasquet et al 2013;Sologuren et al 2018), IRF7 (Ciancanelli et al 2015), IRF9 (Hernandez et al 2018), and TLR3 (Lim et al 2019) deficiencies-have been shown to cause life-threatening influenza pneumonitis (Table 1). Autosomal dominant (AD) GATA2 deficiency is the only one of these IEIs leading to a pleiotropic syndromic disorder that manifests as a lack of multilymphoid and granulocyte-macrophage progenitors in the bone marrow, smaller numbers of dendritic cells (DCs), monocytes, T, B and NK lymphocytes in peripheral blood, and higher susceptibility to viral, mycobacterial, and fungal infections.…”
Section: Inherited Gata2 Deficiencymentioning
confidence: 99%
“…Unlike patients with GATA2 deficiency, those with autosomal recessive (AR) IRF7 and AR IRF9 deficiencies have an almost isolated susceptibility to influenza (Ciancanelli et al 2015;Hernandez et al 2018;Lim et al 2019), albeit only a few patients have been studied so far (Table 1). Only a few signs of broader vulnerability to viruses, including the vaccine strain of measles, have been observed (Ciancanelli et al 2015;Hernandez et al 2018).…”
Section: Inherited Irf7 and Irf9 Deficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, genetic susceptibility to devastating influenza does not appear to be a polygenic trait, but is determined by defects in single genes that govern non-redundant pathways of type I (α/β) and type III (λ) interferon (IFN) responses. Critical genes identified so far are either involved in induction of type I and type III IFNs (TLR3, IRF7) (Ciancanelli et al 2015;Lim et al 2019), IFN production by plasmacytoid dendritic cells (GATA2) (Sologuren et al 2018) or are part of the IFN signaling pathway required for antiviral action (IRF9) . Surprisingly, however, no clear defects have yet been found in type I and type III IFN-stimulated genes (ISGs).…”
Section: Introductionmentioning
confidence: 99%
“…In AD disorders due to HI, the mutant copy is not functional and does not interfere with the WT product, and the single functional WT copy produces too little protein to fulfill its function. HI is more commonly associated with loss-of-expression alleles and DN with normally or highly expressed alleles, but rare examples have been reported of HI with normal levels of the mutant protein (30), and of negative dominance (ND) with a lack of detectable mutant protein (31). Autosomal dominance by GOF defines a third category, in which the mutant protein is produced (32).…”
Section: Haploinsufficient Genes Are Under Stronger Selection Than Domentioning
confidence: 99%